Pengaruh Kompetensi Sumber Daya Manusia dan Penerapan Sistem Akuntansi Keuangan Pemerintah Daerah terhadap Kualitas Laporan Keuangan Dinas Kehutanan Provinsi Lampung - Andri Eka Yunindra (Universitas Mitra Indonesia, 2020)
The purpose of this research to knowing the Competence of Human Resources And Application of Local Government Financial Accounting System Against the Quality of Financial Statements of the Forestry Service of Lampung Province. Data were collected by field research and literature study. To get data related to the problem under study, the author uses the technique of collecting data through questionnaire method. The population in this study as many as 70 people. The sampling technique used is simple random sampling, the number of samples in this study as many as 60 respondents. The data has been collected and then analyzed using spss version 20.The criteria of f test as follows: Fcount Ftable or sign, 0.05 and Fcount Ftable or sign 0.05.means a sign model so that it can be used to predict the effect of independent variables simultaneously to the dependent variable. The result of f test analysis has a significant influence between human resource competence (X1) and SAKPD (X2) implementation simultaneously on Quality of financial report of Forestry Service of Lampung Province. (Y). If thitung ttable, then H0 is rejected, If thitung ttabel, then H0 accepted. The result of t test analysis shows that partially competence of human resources and the application of financial accounting system of local government has a significant effect on the quality of financial report of Lampung Province Forestry Service as big as.